Regenerative Therapy by Suprachoroidal Cell Autograft in Dry Age-related Macular Degeneration: Preliminary In Vivo Report - Limoli, Paolo Giuseppe (J Vis Exp, 2018)
This study is aimed at examining whether a suprachoroidal graft of autologous cells can improve best corrected visual acuity (BCVA) and responses to microperimetry (MY) in eyes affected by dry Age-related Macular Degeneration (AMD) over time through the production and secretion of growth factors (GFs) on surrounding tissue. Patients were randomly assigned to each study group. All patients were diagnosed with dry AMD and with BCVA equal to or greater than 1 logarithm of the minimum angle of resolution (logMAR). A suprachoroidal autologous graft by Limoli Retinal Restoration Technique (LRRT) was carried out on group A, which included 11 eyes from 11 patients. The technique was performed by implanting adipocytes, adipose-derived stem cells obtained from the stromal vascular fraction, and platelets from platelet-rich plasma in the suprachoroidal space. Conversely, group B, including 14 eyes of 14 patients, was used as a control group. For each patient, diagnosis was verified by confocal scanning laser ophthalmoscope and spectral domain-optical coherence tomography (SD-OCT). In group A, BCVA improved by 0.581 to 0.504 at 90 days and to 0.376 logMAR at 180 days (+32.20%) postoperatively. Furthermore, MY test increased by 11.44 dB to 12.59 dB at 180 days. The different cell types grafted behind the choroid were able to ensure constant GF secretion in the choroidal flow. Consequently, the results indicate that visual acuity (VA) in the grafted group can increase more than in the control group after six months.